Carbon sequestration potential of different forest types in Pakistan and its role in regulating services for public health - Ali, Shahab; Khan, Shujaul Mulk; Ahmad, Zeeshan; Siddiq, Zafar; Ullah, Abd; Yoo, Sunghoon; Han, Heesup; Raposo, António (Frontiers in Public Health, 2023)
A high amount of CO2 causes numerous health effects, including headaches, restlessness, difficulty in breathing, increased heart rate, high blood pressure, asphyxia, and dizziness. This issue of increasing atmospheric CO2 can only be solved via above-ground and below-ground carbon sequestration (CS). This study was designed to determine the relationship between CS with the crown area (CA), diameter at breast height (DBH), height (H), species richness (SR), and elevation in different forest types of Pakistan with the following specific objectives: (1) to quantify the direct and indirect relationship of carbon sequestration with CA, DBH, H, and SR in various natural forest types and (2) to evaluate the effect of elevation on the trees functional traits and resultant CS. We used the linear structural equation model (SEM) for each conceptual model. Our results confirmed that the highest CS potential was recorded for dry temperate conifer forests (DTCF) i.e., 52.67%, followed by moist temperate mix forests (MTMF) and sub-tropical broad-leaved forests (STBLF). The SEM further described the carbon sequestration variation, i.e., 57, 32, 19, and 16% under the influence of CA (β = 0.90 and P-value < 0.001), H (β = 0.13 and p-value = 0.05), DBH (β = 0.07 and p-value = 0.005), and SR (β = −0.55 and p-value = 0.001), respectively. The individual direct effect of SR on carbon sequestration has been negative and significant. At the same time, the separate effect of CA, DBH, and H had a positive and significant effect on carbon sequestration. The remaining 20% of CS variations are indirectly influenced by elevation. This means that elevation affects carbon sequestration indirectly through CA, DBH, H, and SR, i.e., β = 0.133 and P-value < 0.166, followed by β = 0.531 and P-value < 0.001, β = 0.007 and P-value < 0.399, and β = −0.32 and P-value < 0.001, respectively. It is concluded that abiotic factors mainly determined carbon sequestration in forest ecosystems along with the elevation gradients in Pakistan. Quantifying the role of various forest types in carbon dioxide (CO2) reduction leads to improved air quality, which positively impacts human health. This is an imperative and novel study that links the dynamics of the biosphere and atmosphere.